Leiomyoma of Achilles tendon sheath with sural neuropathy: a rare cause of lateral foot pain - Tapas Mohanty; Konchada Srikant; Sandeep Pradhan; Preethiv Rajendran (Journal of the Foot & Ankle)
Leiomyomas are well-known benign tumors of uterine smooth muscles. However, leiomyomas are rarely reported in the extremities, particularly in the foot and ankle. We present a case of a 52-year-old woman who presented to our outpatient clinic with complaints of nodular swelling in the posterior aspect of her left ankle with pain and tingling numbness in the lateral aspect of her foot. The excisional biopsy of the mass revealed leiomyoma, a smooth muscle origin tumor. Level of evidence IV; Therapeutic study; Case report.